Social media influencers and digital economy: moving forward - Rosli, Mohamad Hafiz; Jahari, Nor Azah; Md Moid, Muzairihana; Hassan, Nor Hazwani (Universiti Teknologi MARA, Terengganu, 2022)
Malaysia is committed to its aim to be a nation’s digital economy. Malaysia’s National Entrepreneurship Policy 2030 (NEP 2030) and Shared Prosperity Vision 2030 plan highlighted the strategies and initiatives towards achieving this aim and in the long term can transform Malaysia to be the heart of Digital ASEAN (Ministry of Entrepreneur Development and Cooperatives, 2019; MAMPU, 2019). From a business perspective, the digital economy has changed the world business landscape and has become a critical component of the business models of the world's largest digital companies such as Amazon, Alibaba and e-bay. Furthermore, digital consumption is becoming more permanently ingrained as a way of life. In 2021, more than 65% of consumers in Malaysia bought the majority of items they needed online instead of going instore (Google, Temasek & Bain and Company, 2021; Narula, 2022). In today’s digital economy, most digitally-powered businesses integrate the usage of social media as the medium of promotion and sales. Social media is the most assessable and convenient platform and is well accepted by Malaysians.